2006
DOI: 10.1183/09031936.06.00015805
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic ventilatory response in successful extreme altitude climbers

Abstract: A very high ventilatory response to hypoxia is believed necessary to reach extreme altitude without oxygen. Alternatively, the excessive ventilation could be counterproductive by exhausting the ventilatory reserve early on.To test these alternatives, 11 elite climbers (2004 Everest-K2 Italian Expedition) were evaluated as follows: 1) at sea level, and 2) at 5,200 m, after 15 days of acclimatisation at altitude. Resting oxygen saturation, minute ventilation, breathing rate, hypoxic ventilatory response, maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 29 publications
(37 reference statements)
4
58
0
Order By: Relevance
“…However, the actual mechanism for any HVR protection remains unknown, and some argue that a strong HVR may form a negative response due to diminishing ventilatory reserve (Bernardi et al, 2006). Ainslie and Poulin (2004) reported that, across individuals, a higher AHVR during acute poikilocapnic hypoxia was associated with a decrease in the acute hypoxic cerebral blood flow response, but propose that this may be due to the hyperventilation already inducing a hypocapnic-induced cerebral vasoconstriction and dampening the possibility for further responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual mechanism for any HVR protection remains unknown, and some argue that a strong HVR may form a negative response due to diminishing ventilatory reserve (Bernardi et al, 2006). Ainslie and Poulin (2004) reported that, across individuals, a higher AHVR during acute poikilocapnic hypoxia was associated with a decrease in the acute hypoxic cerebral blood flow response, but propose that this may be due to the hyperventilation already inducing a hypocapnic-induced cerebral vasoconstriction and dampening the possibility for further responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilation rapidly increases upon acute hypoxic exposure, and this hypoxic ventilatory response (HVR) is generally presumed to enable better performance at altitude by maintaining arterial oxygen saturation levels (Schoene et al, 1984;Masuyama et al, 1986). Alternatively, a strong HVR has also been proposed to be a negative adaptation that reduces ventilatory reserve at altitude (Bernardi et al, 2006), while hyperventilation and the resultant hypocapnia may reduce cerebral blood flow (Poulin et al, 2002;Ainslie and Poulin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, observations from the 2004 Everest-K2 Italian Expedition are of interest. That is, those climbers who reached the summit without oxygen evidenced a lower restingV E and hypoxic ventilatory responsiveness (HVR, V E − SpO 2 ) during acclimatization (Bernardi et al, 2006); it being proposed that a less sensitive HVR at HA might increase BR and therefore reduce dyspnea to allow sustainableV E 's in the extreme hypoxia at the summit. It should be noted that the observations of Bernardi and coworkers are in contrast those of Schoene et al (1984) who observed a better climbing performance in those subjects with a higher HVR at HA.…”
Section: Ventilatory Limitation and Dyspneic Sensationmentioning
confidence: 99%
“…Exposure to hypoxia [e.g., high altitude; (Bernardi et al 2006;Forster et al 1971;Reeves et al 1993;Sato et al 1994) or intermittent hypoxia (Ainslie et al 2003;Garcia et al 2000;Katayama et al 1998;Levine et al 1992;Mahamed and Duffin 2001;Ricart et al 2000)] results in an elevated ventilatory sensitivity to hypoxia and subsequent hypocapnia. Studies have shown that, despite an elevation in ventilatory chemosensitivity following intermittent hypoxic exposure (IHE), there are no related gas exchange alterations during maximal exercise (Foster et al 2005;Katayama et al 2001); these findings point to a lack of ''carry-over'' effect of a hypoxic-induced elevation in ventilatory chemosensitivity on respiratory responses to normoxic exercise.…”
Section: Introductionmentioning
confidence: 99%